“Changing trends of Candidemia and antifungal susceptibility pattern in a tertiary health care centre:” - Chaudhary, Uma; Goel, Shagun; Mittal, Seema (Infectious Disorders - Drug Targets, 2015)
Background: Bloodstream infections (BSI) caused by various Candida spp. are a significant cause of morbidity and mortality in hospitalized patients. An increasing proportion of device- related infections, particularly those involving the bloodstream and urinary tract, are being caused by Candida spp. Aims and objectives: This study was conducted to evaluate the different species of Candida causing blood stream infections and their antifungal susceptibility. Material and methods: The present study was conducted on 12464 blood samples received for culture, the samples were incubated at 37ºC for overnight and inoculated on culture plate next day. The growth on culture plates was identified by standard microbiological techniques and their antifungal susceptibility was put up as per Centre for Laboratory Standard Institute guidelines. Results: Out of 12464 blood samples, isolation rate of Candida spp was 7.25%, which was higher in paediatric age group patients (89%) as compared to adults (11%). BSIs due to Candida spp. was significantly more common among ICUs (72%) than non-ICU settings (28%). C. tropicalis was the commonest (43%) species isolated followed by C. albicans (41%), C. krusei (9%) and C. parapsilosis (7%). All strains were 100% sensitive to Amphotericin B. Conclusion: There is a changing trend of increased isolation of non albicans Candida spp. than Candida albicans. It was common in ICUs settings and in paediatric age group. All isolates were found 100% sensitive to Amphotericin-B, C.krusei was 100% resistant to fluconazole followed by C. tropicalis 32.6% and C. parapsilosis 28.58%.
Keywords: drug resistance